Hexamethylene diisocyanate (HDI)-functionalized electrolyte matching LiNi0·6Co0·2Mn0·2O2/graphite batteries with enhanced performances. (20th August 2020) - Lu, Jing; Wang, Wenlian; Yang, Tianxiang; Li, Shuai; Zhao, Xiaoyang; Fan, Weizhen; Fan, Chaojun; Zuo, Xiaoxi; Nan, Junmin
Abstract: Hexamethylene diisocyanate (HDI)-functionalized electrolyte is demonstrated that it can decrease the electrolyte HF content, form the stable electrode interfaces, and improve the performances of LiNi0·6 Co0·2 Mn0·2 O2 (NCM622)/graphite batteries. The capacity of the battery with blank electrolyte decreases sharply at a 1C rate after 230 cycles, while the battery with 0.1% HDI-functionalized electrolyte exhibits stable discharge capacity and an increase of capacity retention rate from 74.7% to 98.4% at the 230th cycle. Specifically, the battery with 0.1% HDI-functionalized electrolyte retains 82.9% initial reversible capacity even after 600 cycles, and also exhibits an excellent rate performance. Based on the analysis of HDI molecules and film-forming mechanism, it is indicated that the HDI molecules in the electrolyte can inhibit the HF generation and participate in the interface formation, which are conducive to reduce the corrosion and impedance and finally improve the electrode stability and battery performances. This work not only obtains a high-performance HDI-functionalized electrolyte but also can provide an effective strategy to develop the functionalized electrolyte matching high-nickel NCM/graphite batteries. Graphical abstract: Image 1 Highlights: Hexamethylene diisocyanate (HDI) in the electrolyte reduces the HF formation and cathode corrosion. HDI-functionalized electrolyte facilitates the formation of high-quality interface films on both electrodes. The interface films can improve the cycle and rate performances of NCM622/graphite batteries. The low-temperature discharge performance of the batteries with HDI can also be improved.